2015
DOI: 10.1371/journal.pone.0127707
|View full text |Cite
|
Sign up to set email alerts
|

BIG3 Inhibits the Estrogen-Dependent Nuclear Translocation of PHB2 via Multiple Karyopherin-Alpha Proteins in Breast Cancer Cells

Abstract: We recently reported that brefeldin A-inhibited guanine nucleotide-exchange protein 3 (BIG3) binds Prohibitin 2 (PHB2) in cytoplasm, thereby causing a loss of function of the PHB2 tumor suppressor in the nuclei of breast cancer cells. However, little is known regarding the mechanism by which BIG3 inhibits the nuclear translocation of PHB2 into breast cancer cells. Here, we report that BIG3 blocks the estrogen (E2)-dependent nuclear import of PHB2 via the karyopherin alpha (KPNA) family in breast cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…Moreover, PHB1 is overexpressed in ovarian epithelial tumors and induces cell proliferation 71 , 72 . In estrogen-dependent cancers such as breast cancer, investigators reported that BIG3, a key molecular regulator in the ER signaling pathway, inhibits the nuclear transportation of the PHB2/REA transcription complex, abolishing the inhibitory effect of the PHB2/REA complex on ERα transcriptional activity 73 , 74 . PHB2 was also shown to promote hepatocellular carcinoma growth and malignancy progression in the hypoxic tumor microenvironment 75 .…”
Section: Role Of Phb1 and Phb2 In Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PHB1 is overexpressed in ovarian epithelial tumors and induces cell proliferation 71 , 72 . In estrogen-dependent cancers such as breast cancer, investigators reported that BIG3, a key molecular regulator in the ER signaling pathway, inhibits the nuclear transportation of the PHB2/REA transcription complex, abolishing the inhibitory effect of the PHB2/REA complex on ERα transcriptional activity 73 , 74 . PHB2 was also shown to promote hepatocellular carcinoma growth and malignancy progression in the hypoxic tumor microenvironment 75 .…”
Section: Role Of Phb1 and Phb2 In Tumorigenesismentioning
confidence: 99%
“…As PHB2 is involved in estrogen-dependent cancers such as breast cancer, and BIG3 promotes cancer cell proliferation by inhibiting PHB2 nuclear translocation and promoting the activity of ERα, the BIG3/PHB2 interaction is necessary for tumorigenesis 73 , 74 . Therefore, inhibition of the interaction of BIG3-PHB2 is a feasible strategy in estrogen-dependent cancer therapy.…”
Section: Value Of Phb1 and Phb2 As Therapeutic Targets In Cancer Treamentioning
confidence: 99%
“…S7 ), it is likely that PHB2 downregulates AQP gene expression. PHB2 translocates to the nucleus with ERα in HeLa and MCF-7 cells and represses ERα-dependent transcription [ 46 , 48 ]. Moreover, ERα up-regulates AQP expression, as mentioned in the Results section [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For identification of an O-glycosylation site(s) on ER-α protein, HeLa-GALNT6 stable cells (WT) were transfected with pCAGGSn3FC-ER-α expression vector [18] , [19] and collected after 48 hours of incubation. Cells were lysed with lysis buffer, and Flag-tagged ER-α protein was immunoprecipitated with anti-Flag monoclonal antibody and Protein A/G agarose (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%